THE DRAWING WASN'T AN ORNAMENT, IT WAS A WRITING - Couy, Venus Brasileira (2008)
This work searchs to articulate the body and the writing. It has those that compare the author with the figure of the tatuador and literature to the tattooing. In this article, the author looks for to verify if we could think the tattooing as a writing. For in such a way, it inquires on what it is the writing, it presents definitions, it covers its history. It still approaches the half material on which the writing is recorded and the used instruments. E retakes the question: the skin human being is a parchment and if it configures, therefore, as registration support? The tattooing is a writing and, as such, can this be readen? When dealing with the question, one mentions citizens to it that had been in search of the tattooing, to the search of the "writing of the tattooing" and had told, in interviews, that they desired, over all, to mark an important event. Finally, the article presents a joint enters the Real of the body, Symbolic of the word and the corporal surface while image. It mentions the edge function, of letter that the tattooing can make – attempt to bar and to circumscribe the joy, forms to deal with the Real the body, this irreducible stranger.